Trois visions de la préfecture du prétoire du Ier au IIIe siecles apres J.-C.Un essai de synthese - Ruciński, Sebastian (Studia Europaea Gnesnensia, 2011)
In the literature of the antiquity we can distinguish three patterns: the minimalist, universalistic and constrained. The first confines prefecture to being merely the command of praetorian cohorts, while other possible functions performed by these officers result only from exceptional and temporary mandate of the emperor. On the other hand, the universalistic model assumes that a prefect, at least potentially, possesses the same powers as the emperor — to be limited only by the presence and the will of the ruler. The third model, presented by Cassius Dio, is an intermediate form — a compromise, which perhaps is fashioned after the practice employed in certain periods, yet in part it was rather a postulate than reality.